Optimal investment in an energy storage system - Marta Castellini; Chiara D'Alpaos; Fulvio Fontini; Michele Moretto (Fondazione Eni Enrico Mattei (FEEM), 2025)
Renewable energy production plays a crucial role in the energy transition. However, many renewable energy sources (RES) are intermittent, and there is often a mismatch between energy production and consumption, which can be partially solved by storage. In this paper, we investigate the investment decision in a photovoltaic (PV) power plant coupled with a Battery Energy Storage System (BESS), namely an Energy Storage System (ESS). We aim to investigate the relationship between the net present value (NPV) of the investment and the technical implications related to the maximum amount of energy to be stored while also accounting for the impact of energy prices. In our setting, the BESS is connected to the national power grid and the PV plant. Energy can be produced, purchased from the grid, stored, self-consumed, and fed into the grid. PV production and energy consumption loads evolve stochastically over time. In addition, as BESS are costly, energy stored has an opportunity cost, which depends on the prices of energy purchased from the grid and energy fed in and sold to the grid, respectively. However, BESS can significantly contribute to increase ESS managerial flexibility and, in turn, ESS value. In detail, we investigate the optimal BESS size that minimizes ESS net operating costs. We also provide insights on ESS optimal management strategy. Our results show that ESS net operating costs are relatively small. They reduce for increasing selling prices of energy, whereas they increase for increasing volatility of the stock of energy stored in the battery.
Keywords: Q42; C61; D81; 330; Renewable Energy Sources; Photo-voltaic; Battery Storage